Scattergories Game on Junior High School Students’ Vocabulary Mastery in Language Learning - Dwi Liza Anggraini; Maryati Salmiah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This article aims to determine the effect of using Scattergories Game on students' vocabulary mastery. The method used is a pre-experimental design with a quantitative approach. The population that was the research subject was 8th grade students at one of the MTs in Sampali. Consisting of 30 students in it. The researcher gave a pre-test - treatment – post-test to all samples to collect the required data. After that, the data was processed using the T-test in SPSS. The result showed that there is a significant influence between variable X on variable Y and decision making because sig .000 <0.05 and the average score on the post test (25.36) was higher than pre-test (13.63). From the results of data processing carried out by researchers, it can be concluded that the Scattergories game has an effect on students' vocabulary mastery Keywords: Effect, Scattergories Game, Vocabulary Mastery